Modeling and Simulation of Bulk Metallic Glass Crystallization During Laser Powder Bed Fusion - Yang, Zerong (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)
Bulk metallic glasses (BMGs) exhibit many exceptional mechanical properties, making them promising structural materials in diverse industries. These properties derive from their characteristic amorphous structure. However, conventional processing technologies, due to limited cooling rates, face challenges in preventing crystallization to maintain amorphous structures. This limitation restricts the fabrication of complex BMG structures with substantial section thickness. Consequently, it remains challenging to realize the full spectrum of attractive properties offered by BMGs through conventional processing technologies. In contrast, laser powder bed fusion (PBF-LB/M), with its rapid cooling rates at the solidification front, shows great promise for manufacturing BMG parts. Yet, to achieve success, it is crucial to develop optimal process strategies that can effectively minimize both crystallization and process defects. Unfortunately, the current lack of understanding regarding BMG crystallization during PBF-LB/M forces us to heavily depend on trial-and-error experiments for process development. This approach, however, is often not only time-consuming but also costly. This thesis aims to attain a profound and comprehensive understanding of the crystallization behavior of BMGs during PBF-LB/M and develop a numerical tool that can significantly assist in the PBF-LB/M process development. The numerical work builds upon our in-house simulation software, SAMPLE2D, originally developed for simulating the electron beam powder bed fusion process. Consequently, this thesis focuses on two key modeling aspects: laser beam absorption and crystallization. Laser beam absorption was modeled using a ray-tracing approach, considering reflection, refraction, and absorption. The emphasis was on calculating the laser beam absorption coefficient, accounting for its dependence on the angle of incidence and temperature, based on fundamental physical laws. Model validation involved comparing simulation-predicted melt pool geometries with experimentally observed ones, revealing a satisfactory agreement between the two. Modeling of the crystallization behavior serves as the core focus of this thesis. Experimentation provided insights into primary physical effects to consider in the modeling efforts. The modeling approach revolved around the utilization of a phenomenological phase transformation model, specifically the Nakamura model. For numerical implementation, a two-step Euler method was devised. Model parameters were determined through isothermal crystallization experiments, providing essential inputs for the simulation. Experimental validation was achieved by comparing single-track-multi-pass and multi-layer PBF-LB/M results with simulation outcomes. Throughout the study, the glass-forming alloy Zr59.3Cu28.8Al10.4Nb1.5 (at.%) was used as a representative example. The robust agreement between experimental and simulation results allowed for the extensive application of the extended SAMPLE2D, enabling a comprehensive investigation of PBF-LB/M process conditions, encompassing beam- and powder bed-related parameters, as well as scanning strategies. Numerical insights unveiled that BMG crystallization during PBF-LB/M is a localized phenomenon primarily induced by short-range in-situ heat treatment. Furthermore, a general process development guideline was proposed: First, utilize an appropriate energy input to minimize porosity; Second, within the parameter space capable of fabricating dense parts, minimize the energy input and select parameters that yield a more even energy distribution; Third, optimize the scanning strategy to further reduce crystallization. Notably, the line jumping scanning strategy was highlighted as an effective means of minimizing crystallization while maintaining relative density. Therefore, this thesis not only deepens our comprehension of BMG crystallization during PBF-LB/M but also furnishes the industry with a readily applicable numerical tool to aid in practical PBF-LB/M process developmen
Keywords: Bulk metallic glass; Crystallization; Laser powder bed fusion (PBF-LB/M); Simulation; Modeling; Additive manufacturing